Relationship between job satisfaction and working conditions moderated by gender - Angel Hernández; Lucirene Rangel-Lyne; Magda Lizet Ochoa-Hernández (Revista de Psicología y Ciencias del Comportamiento de la Unidad Académica de Ciencias Jurídicas y Sociales)
There is an opportunity to delve deeper into the topic of the effects of working conditions on job satisfaction from the perspective of gender studies. Therefore, this article aims to analyze the relations-hip between working conditions and job satisfac-tion and the moderating effect of gender. A self-administered survey was used for a sample of wor-kers from hotel companies in the Southern Metro-politan Area of Tamaulipas. The data collected was analyzed through the moderation model with the help of the PROCESS interface, in the statistical software SPSS Statistics version 24, performing a moderation for each scale of working conditions (environmental, ergonomic and economic) in rela-tion to intrinsic satisfaction and extrinsic. The re-sults show significant effects between environmen-tal and ergonomic working conditions on intrinsic and extrinsic job satisfaction, while economic working conditions do not show significant effects on any type of satisfaction. Regarding gender, this only moderates the relationship between environ-mental working conditions and intrinsic job satisfaction.